2019
DOI: 10.3390/foods8010021
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperuricemia, Antioxidant, and Antibacterial Activities of Tridax procumbens L.

Abstract: Tridax procumbens L. is a medicinal plant and used as a drink to treat bronchial catarrh, diarrhea, dysentery and liver diseases. In this study, we evaluated the potential use of T. procumbens to treat hyperuricemia, oxidative stress, and bacterial infection. Ethyl acetate extract of this plant was separated to different fractions by column chromatography (CC) using chloroform and methanol as eluents and subjected to xanthine oxidase (XO) inhibitory, antioxidant, and antibacterial assays. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 38 publications
0
31
0
2
Order By: Relevance
“…A previous study showed that aqueous extraction is not as potent as extractions using organic solvents. Andriana et al (2019) reported that hot water extract of Tridax procumbens L. showed no inhibition activity against the tested microbes. This study confirmed earlier observations that either polar or nonpolar solvents had the capacity to produce a large number of bioactive molecules (Sujatha & Suresh, 2013;Tiwari, Kumar, Kaur, Kaur, & Kaur, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that aqueous extraction is not as potent as extractions using organic solvents. Andriana et al (2019) reported that hot water extract of Tridax procumbens L. showed no inhibition activity against the tested microbes. This study confirmed earlier observations that either polar or nonpolar solvents had the capacity to produce a large number of bioactive molecules (Sujatha & Suresh, 2013;Tiwari, Kumar, Kaur, Kaur, & Kaur, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The xanthine oxidase (XO) inhibitory activity was assayed spectrophotometrically in vitro under aerobic condition according to the method reported previously [46,47]. Briefly, a volume of 50 µL sample or standard was mixed with 35 µL of 70 mM phosphate buffer (pH = 7.5), and 30 µL of fresh xanthine oxidase solution (0.01 units/mL in 70 mM phosphate buffer, pH = 7.5) in a 96-well microplate.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical composition of P. cubeba and P. nigrum EOs detected in GC-MS system both for volatile and non-volatile components were confirmed by LC-ESI-MS system (Thermo Fisher Scientific TM , LTQ XLTM, Ion Trap Mass Spectrometer, Tokyo, Japan) [47]. The column used for the LC system was a JASCO J-Pak Symphonia C18 (250 mm × 4.6 mm × 5 μm).…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant activity of extracts and isolated fractions were estimated by DPPH free radical scavenging method described by [15]. In details, a mixture contained 0.5 mL of each sample, 0.25 mL of 0.5 nM DPPH, and 0.5 mL of 0.1 M acetate buffer (pH 5.5) was prepared and placed in the dark for 30 min at ambient conditions.…”
Section: Methodsmentioning
confidence: 99%